The effects of strength training versus ski-ergometer training on double-poling capacity of elite junior cross-country skiers - Carlsson, T.; Wedholm, L.; Nilsson, J.; Carlsson, M. (European Journal of Applied Physiology, 2017)
Purpose: To compare the effects of strength training versus ski-ergometer training on double-poling gross efficiency (GE), maximal speed (V max), peak oxygen uptake (VO2peak) for elite male and female junior cross-country skiers. Methods: Thirty-three elite junior cross-country skiers completed a 6-week training-intervention period with two additional 40-min training sessions per week. The participants were matched in pairs and within each pair randomly assigned to either a strength-training group (STR) or a ski-ergometer-training group (ERG). Before and after the intervention, the participants completed three treadmill roller-skiing tests to determine GE, V max, and VO2peak. Mixed between-within subjects analysis of variance (ANOVA) was conducted to evaluate differences between and within groups. Paired samples t tests were used as post hoc tests to investigate within-group differences. Results: Both groups improved their V max and VO2peak expressed absolutely (all P < 0.01). For the gender-specific sub-groups, it was found that the female skiers in both groups improved both V max and VO2peak expressed absolutely (all P < 0.05), whereas the only within-group differences found for the men were improvements of V max in the STR group. No between-group differences were found for any of the investigated variables. Conclusions: Physiological and performance-related variables of importance for skiers were improved for both training regimes. The results demonstrate that the female skiers` physiological adaptations to training, in general, were greater than those of the men. The magnitude of the physiological adaptations was similar for both training regimes.